# Solve for p 2p-5(p-4)=2p+12

2p-5(p-4)=2p+12
Simplify 2p-5(p-4).
Simplify each term.
Apply the distributive property.
2p-5p-5⋅-4=2p+12
Multiply -5 by -4.
2p-5p+20=2p+12
2p-5p+20=2p+12
Subtract 5p from 2p.
-3p+20=2p+12
-3p+20=2p+12
Move all terms containing p to the left side of the equation.
Subtract 2p from both sides of the equation.
-3p+20-2p=12
Subtract 2p from -3p.
-5p+20=12
-5p+20=12
Move all terms not containing p to the right side of the equation.
Subtract 20 from both sides of the equation.
-5p=12-20
Subtract 20 from 12.
-5p=-8
-5p=-8
Divide each term by -5 and simplify.
Divide each term in -5p=-8 by -5.
-5p-5=-8-5
Cancel the common factor of -5.
Cancel the common factor.
-5p-5=-8-5
Divide p by 1.
p=-8-5
p=-8-5
Dividing two negative values results in a positive value.
p=85
p=85
The result can be shown in multiple forms.
Exact Form:
p=85
Decimal Form:
p=1.6
Mixed Number Form:
p=135
Solve for p 2p-5(p-4)=2p+12

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top